Syncope as initial symptom of ostial lesion of the left main coronary artery with cardiogenic shock - Petrović, Milovan; Ivanov, Igor; Vujin, Bojan; Ivanović, Vladimir; Redžek, Aleksandar (Vojnosanitetski pregled, 2014)
Introduction. Syncope represents a relatively atypical symptom of acute coronary syndrome. Syncope itself does not provide enough information to indicate an acute coronary event, especially a lesion of the left main coronary artery, without malignant rhythm and conduction disorders. Case report. A male patient, aged 63, was admitted to the intensive cardiac care unit because of a short loss of consciousness, in sinus tachycardia, with signs of acute heart failure and being hypotensive. Electrocardiogram showed a possible acute anterior myocardial infarction, followed by cardiogenic shock and emergency coronary angiography (subocclusive ostial lesion of the left main coronary artery) and primary percutaneous coronary intervention with intra-aortic balloon pump therapy was performed. A direct drug eluting stent was implanted with the optimal primary result. Conclusion. The prompt diagnosis, especially in such relatively atypical clinical presentation, reperfusion therapy with primary percutaneous coronary intervention in acute myocardial infarction complicated by cardiogenic shock, contribute to the improvement in the survival rate and patient’s quality of life. This case report is clinically educative due to relatively atypical presentation and performed interventions.